Mario de Andrade and Claude Debussy - Coli, Jorge (Revista do Instituto de Estudos Brasileiros, 1994)
This essay is builts upon the analysis of two texts belonging to Mário de Andrade´s series O Mundo Musical. It demonstrates the role and importance of Claude Debussy´s works on Mário de Andrade´s thought from 1921 until the author´s final days contrassing with romantic notions and notions of socially committed art held by Mário de Andrade, and giving rise to an open work.